PENGEMBANGAN RPP (RENCANA PELAKSANAAN PEMBELAJARAN) BERBASIS PENDIDIKAN KARAKTER - Ibnu Chudzaifah; Afroh Nailil Hikmah (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2019)
Character education has a higher meaning than moral education, because character education is not only related to right and wrong problems, but how to instill habits (habituation) about things that are good in life, so that students have high awareness, sensitivity, and understanding , as well as concern and commitment to apply virtue in everyday life. Thus it can be said that a person with character is a person's nature in responding to situations in a moral way, manifested in real action through good behavior, honesty, sincerity, responsibility, respect for others and other noble character values. Therefore, as a teacher, it should be able to apply character education to the learning process. In this paper, the authors offer ideas or concepts in the preparation of a comprehensive character education based learning plan (RPP).